Pengaruh Struktur Modal Terhadap Nilai Perusahaan Dengan Pertumbuhan Perusahaan Sebagai Variabel Moderating Pada Perusahaan Consumer Goods Industry di Bursa Efek Indonesia Tahun 2010-2012 - Azwir, Ayu Adriany; Ilham, Elfi; ', Zulbahridar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The company was established with the aim to prosper company owners or shareholders. This goal can be achieved by maximizing the value of the company. Value of the company is a condition that has been achieved as a description of public confidence in the company through a process activity for several years, that is since the company was founded until now. This study aims to obtain empirical evidence about the effect of capital structure on firm value with the growth of the company as a moderating variable.This research was conducted in the consumer goods industry companies listed in Indonesia Stock Exchange.This study uses the data in the period of 2010 to 2012. Sampling technique is to use a purposive sampling method, that is by using certain criteria. Determination of the criteria necessary to determine that the sample selected samples will provide the data needed in the analysis process. The analysis used is multiple regression analysis (multiple regression) with the enter method using SPSS statistical software version 17.00.The results of this study indicate that the variables shown to influence the growth of the company enterprise value (p <0.05) β = 3,011, while the variable capital structure does not affect the value of the company. While the effect of capital structure on firm value with growth companies as moderating variables also have a significant effect seen on the significance of F at 6.124 and 0.04 (<0.05). The amount Adjested R Square is equal to 0.163 berari capital structure and company growth can explain the value of the company amounted to 16.3%. and the remaining 83.7% is explained by other variables not examined in this study.Keywords: Value Company, capital structure and the Company's growth.